ROLE OF PEDAGOGICAL CULTURE AND PROFESSIONAL IDENTITY IN FORMATION OF READINESS FOR PROFESSIONAL PEDAGOGICAL SELF-DEVELOPMENT UNDERGRADUATES IN HIGHER EDUCATION - Fedchenko, Y. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. The article is emphasized social importance and necessity of formation of pedagogical culture and promoting the professional identity of undergraduates pedagogical readiness to form to professional self-development of future teachers during their studies in higher education. Revealed the presence of underestimating importance of teaching culture and professional identity in the process of readiness graduate pedagogical to the professional self-development while studying in higher education and therefore determined that one of the important tasks of training future teachers of higher educational institutions at the current stage of development of Ukrainian society proper organization of educational process undergraduates zprofesiynoyi identity. Revealed that during training future academics are learning techniques and technology educational work. However, for the formation of readiness for professional self-pedagogical undergraduates while studying in higher education institutions must also provide students the opportunity to use a professional identity on the basis of their educational culture. Thus, one of the major problems of formation of readiness for professional self-development of pedagogical graduate to professional self-development at the present stage of development of Ukrainian society is the proper organization of the conditions of the educational process in higher educational institutions and help in establishing a professional identity. Purpose of the article - to consider the problem of formation of readiness for professional self-development graduate pedagogical, and providing appropriate support in achieving the appropriate level of educational and professional culture of self-development. Results. The ability to adjust the educational process taking into account the cultural foundations of teaching, increase its level of pedagogical undergraduates while studying in higher education contributes to the process of their professional identity and forms readiness for professional self-development. The results of the testing confirmed this category of students. Originality. We believe that this approach is essential for the future high school teachers. He directs and promotes their ability to be able to perform professional activities. The proposed definition of professional identity corrects and directs in achieving the goal of undergraduates to the formation of pedagogical readiness for professional self-development. Conclusion. Thus, while studying in higher education undergraduates learn pedagogical methods and techniques of professional self-development on the basis of professional identity considering their level of educational culture. Have the opportunity to adjust their level of educational culture, thereby contributing to the formation of their readiness for professional self-development and execution of professional activity at an appropriate level